13 Impact of the 2019 ESC chronic coronary syndrome guidelines publication, on referrals for coronary imaging in a chest pain service. (30th September 2020) - Waters, M; O' Conor, C; Offiah, G; Ingram, S; Loo, B
Abstract : On August 31st 2019 the ESC guidelines for the diagnosis and management of chronic coronary artery syndrome was published. The guidelines give a greater emphasis on the use CT coronary arteries (CTCA) in the work-up of obstructive coronary artery disease (CAD). In addition, the use of exercise stress testing (EST) in establishing a diagnosis of coronary artery disease was downgraded from Class I recommendation to Class IIb. The guidelines also reduced the pre-test probability (PTP) of obstructive coronary artery disease in symptomatic patients according to age, sex and nature of symptoms. However, currently the additive effects of risk factors and EST is unknown. The aim of this study was to assess whether publication of the ESC 2019 guidelines had an effect on referrals for further coronary imaging in patients that were referred to the chest pain service, without a history of coronary artery disease. Methods: A retrospective review of patients referred to the chest pain service in 2019. Only patients without a prior history of coronary artery disease, with negative troponins and without dynamic ECG changes were included in our analysis. All patients underwent exercise stress testing at baseline. A comparison of referrals for invasive coronary angiogram or CTCA, between the periods of January 1st 2019 – 31st of August, with September 1st - 31st December 2019 post publication of the ESC guidelines was made. PTP was calculated via the 2019 ESC guidelines. Results: The analysis includes 330 patients referred to the chest pain services without a prior history of coronary artery disease. Baseline characteristics; 49.39% male, mean age 55.3 yrs, negative EST 68.8%, baseline PTP 10%. Further coronary imaging was selected in 45.7% (n = 151) of patients seen by the chest pain service in 2019, mean PTP 12%. Prior to publication of the ESC guidelines, further coronary imaging was performed in 41.30% of patients seen by the chest pain services; compared to 57.2% after the publication of the ESC guidelines, p-value 0.02. The increase in imaging referrals reflect the increased use of CTCA post guideline publication, 16.4% vs 29.5%, p-value 0.003. CTCA was performed mainly in patients with low PTP mean 7.5%, non-anginal chest pain 83.8% (n = 57) and negative EST 92.6% (n = 63). The incidence of obstructive CAD in our cohort was 9.2% (n = 14); mean PTP 18%, 84.6% positive EST. The negative predictive value of a negative or sub-maximal EST was 98.13% in our cohort who had further imaging (95% CI 92.8 – 99.4%). Discussion: The publication of the ESC 2019 guidelines on chronic coronary syndromes, coincided with an increase in CTCA referrals by 180% in the chest pain service. The overall incidence of obstructive coronary artery disease was low, which is likely reflected by the low PTP in this cohort. Our results underline the utility of EST in risk assessing the probability of obstructive CAD in this cohort, however physicians need to understand its diminished role in the diagnosis of coronary artery disease.